The right to the City (Centre): a spatial development framework for affordable inner-city housing in Cape Town's Foreshore - Weber, Megan (School of Architecture, Planning and Geomatics, 2018)
There is a spatial dislocation between jobs and people in Cape Town, which is largely caused by financial exclusion through urban land markets. The majority of low-income households - who also constitute the majority of the city's population - live on the urban periphery, where property is affordable but opportunities are scarce. This places the burden of high transport costs on the shoulders of those least able to pay, and reinforces the patterns of segregation imposed by apartheid. This deep-rooted spatial inequality has recently been brought to the fore through a series of housing-related protests by Reclaim The City and others. These movements prove that the need for well-located, affordable housing is only getting more urgent. If Cape Town is to overcome the spatial legacy of apartheid, it needs more affordable housing in areas of economic and social opportunity. This dissertation demonstrates how affordable housing can be provided in one well-located, inner-city site: The Foreshore. Situated in the City Bowl, the Foreshore is close to the abundance of employment opportunities and social facilities of this established and growing district. Further, the City of Cape Town has recently begun a tender process for development of the Foreshore. This included a request (albeit vague) for affordable housing to be included in the resulting project. Building on the City's intentions, this dissertation presents a spatial development framework for the Foreshore site that prioritises affordable housing and a mix of uses. The need for affordable, inner-city housing was established through an analysis of Cape Town and the City Bowl. Through this analysis, the Foreshore emerged as a prime site for fulfilling this need. A review of housing policy and legislation, together with an assessment of Cape Town's housing market, determined that Social Housing is the best model for achieving sustainable affordability in an urban context. However, it was found that the involvement of private sector is crucial to realising developments that are feasible and diverse. Further, it is important to take a demand-driven approach to housing delivery, which is sensitive to market nuances and which draws on a range of spatial planning principles. This helps to create holistic, liveable neighbourhooods. These principles were demonstrated in the spatial development framework for the Foreshore. This showed that developing the Foreshore presents an opportunity to reintegrate society, and to reconnect the city to the sea. It is possible to develop 8500 residential units in the site, most of which would be affordable to households earning R3500 to R15000 per month. To achieve this, it is vital that the elevated freeways be replaced with ground-level roads, which will in fact reduce traffic congestion. The city's historical connection to the sea should be restored by reconstructing the Adderley Pier and creating a Foreshore promenade. Realising these projects in manner that is feasible, sustainable, and socially just would require an efficient and tactical implementation process. Discussions with experts in the field of affordable housing development revealed some key implementation strategies for this. These included the package of plans process, land value capture, and the strategic use and release of state-owned land. Together, these would enable the controlled involvement of private sector in the Foreshore development, and would help to find the project's infrastructure. These findings are not entirely exclusive to the Foreshore, and could therefore give guidance to affordable housing projects in other parts of the City Bowl. Therefore, developing the Foreshore to prioritise affordable housing could initiate the socio-spatial reintegration of Cape Town's fragmented city centre.